2020
DOI: 10.3390/microorganisms8091452
|View full text |Cite
|
Sign up to set email alerts
|

Chlorine Disinfection of Legionella spp., L. pneumophila, and Acanthamoeba under Warm Water Premise Plumbing Conditions

Abstract: Premise plumbing conditions can contribute to low chlorine or chloramine disinfectant residuals and reactions that encourage opportunistic pathogen growth and create risk of Legionnaires’ Disease outbreaks. This bench-scale study investigated the growth of Legionella spp. and Acanthamoeba in direct contact with premise plumbing materials—glass-only control, cross-linked polyethylene (PEX) pipe, magnesium anode rods, iron pipe, iron oxide, pH 10, or a combination of factors. Simulated glass water heaters (SGWHs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 68 publications
(101 reference statements)
0
15
0
Order By: Relevance
“…Attenuated (Δ cpxA ) and infectious (WT) Lp (described in Table ) were the most susceptible to both disinfectants, while the highly infectious cells (Mg-Spike and Protozoan-Primed) were the most resistant to both disinfectants. Interestingly, Martin et al found little efficacy of free chlorine treatment of Lp in the presence of a magnesium anode as compared to its absence in simulated glass water heaters containing 1 mg/L total organic carbon …”
Section: Resultsmentioning
confidence: 99%
“…Attenuated (Δ cpxA ) and infectious (WT) Lp (described in Table ) were the most susceptible to both disinfectants, while the highly infectious cells (Mg-Spike and Protozoan-Primed) were the most resistant to both disinfectants. Interestingly, Martin et al found little efficacy of free chlorine treatment of Lp in the presence of a magnesium anode as compared to its absence in simulated glass water heaters containing 1 mg/L total organic carbon …”
Section: Resultsmentioning
confidence: 99%
“…PVC pipes generally have lower scale potential than metal pipes [ 26 ]. Surprisingly, chlorine concentration values in the warmest part of the year (3rd quarter) were significantly higher than in the 1st and 4th quarters, considering that higher water temperature accelerates the rate of chlorine degradation in water distribution systems [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…Variations in water temperature throughout the hydraulic circuit of the installation, together with stagnation and the presence of biofilms or biolayers, calcareous incrustations, corrosion or mineral precipitates, are factors that favour the proliferation of Legionella [ 31 , 32 ]. Likewise, the materials that make up the hydraulic circuit must resist the aggressive action of water and chlorine or other disinfectants to avoid corrosion phenomena [ 33 ]. Materials that favour the development of bacteria and fungi, such as leather, wood, fibre cement, concrete or cellulose derivatives, should be avoided.…”
Section: Discussionmentioning
confidence: 99%